Research on the Influence of Shallow Buried Tunnel Crossing on the Stability of Overlying Frame Structure Building - Bo Wang; Suizi Jia; Mingyi Han; Jingkai Qu; Huimin Gong; Chao Lu; Ziming Qu (Journal of Marine Science and Engineering)
The land section of the Huangdao end of the Jiaozhou Bay Second Submarine Tunnel is extensively underlain by the Quaternary Loose Accumulation Layer. The tunnel passes through a weathered granite fracture zone with well-developed rock joints beneath the buildings. The tunnel excavation process significantly disturbs the buildings above, making them prone to settlement, cracking, and tilting. This research conducts numerical simulations of three tunnel excavation methods, and based on the results, compares the deformation behaviors of the ground surface and buildings under various conditions. The findings show that the double side-wall guide pit method has better adaptability in controlling surface settlement and building deformation than the vertical or curved CD method. Moreover, the removal of temporary supports significantly affects building settlement and tilt; this risk can be effectively reduced by controlling the stress relief ratio during the removal phase of the temporary supports in the tunnel. The significance of the study lies in the fact that by choosing an appropriate tunnel excavation support scheme, the disturbance impact on the overlying buildings can be minimized, and the construction safety and stability of the surrounding buildings can be guaranteed. The results of this study can provide initial guidance for constructing shallow-buried tunnels beneath existing buildings.